Effect of wetted surface area on friction, pressure, wave and total drag of a kayak - Gomes, B. B.; Machado, L.; Ramos, N. V.; Conceicao, F. A. V.; Sanders, R. H.; Vaz, M. A. P.; Vilas-Boas, J. P.; Pendergast, D. R. (Sports Biomechanics, 2018)
Using theoretical principles, the components of drag (friction D F, pressure D PR and wave D W) of a single-seat kayak were analysed. The purpose was to examine the effect of changes in wetted surface area due to changes in kayaker`s weight and the relative contribution of D F, D PR and D W to the total passive drag as function of velocity. The total passive drag values were based on experimental data collected in a single-seat kayak. Three different kayaker simulated weights were tested - 65, 75 and 85 kg. D F was the drag component that contributed the greatest percentage (between 60 and 68% at 5.56 m/s the top velocity tested) to the total passive drag for all the velocities tested and simulated weights. D W was the most affected by the increase in kayaker`s simulated weight, mainly when comparing 65/75 to 85 kg. Results support the importance of a kayak design selection that minimises the kayak`s drag for the individual weight of the kayaker. Also, the results suggest that the path for better hydrodynamic kayak performance should seek changes that can reduce D F, D PR and D W with D F offering the most potential to reduce passive drag.